Ответ:
Объяснение:
Дано:
m₁ = 64 кг
m₂ = 27 кг
L = 4 м
_________
X - ?
По правилу моментов:
F₁·X = F₂·(L - X)
m₁·g·X = m₂·g·(L - X)
m₁·X = m₂·(L - X)
m₁·X = m₂·L - m₂·X
(m₁ + m₂)·X = m₂·L
X = m₂·L / (m₁ + m₂)
X = 27·4 / (64 + 27) ≈ 1,2 м
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
Дано:
m₁ = 64 кг
m₂ = 27 кг
L = 4 м
_________
X - ?
По правилу моментов:
F₁·X = F₂·(L - X)
m₁·g·X = m₂·g·(L - X)
m₁·X = m₂·(L - X)
m₁·X = m₂·L - m₂·X
(m₁ + m₂)·X = m₂·L
X = m₂·L / (m₁ + m₂)
X = 27·4 / (64 + 27) ≈ 1,2 м